FINANCIAL INNOVATION IN CONVENTIONAL BANKING IN INDONESIA - Sholikha Oktavi Khalifaturofi'ah (Fakultas Ekonomi dan Bisnis Universitas Padjadjaran, 2020)
This study aims to examine the relationship between the level of cost efficiency and financial innovation in conventional banks in Indonesia. The data used is panel data from conventional banks during the period 2009-2017. The research method used is the multinomial logit regression method. The dependent variable used is financial innovation consisting of a dummy application of ATMs, internet banking, and mobile banking. The explanatory variables used include cost efficiency, bank size, number of branches, bank age, and ownership. The research results show that cost efficiency, bank size, number of branches, and bank age have a significant effect on financial innovation. An efficient bank, a large bank size, a small number of branches, and a young bank age have an influence on financial innovation in conventional banks by providing ATMs, internet, and mobile banking. Bank ownership has no significant effect on financial innovation in conventional banks.